Gambaran Perbandingan Pemeriksaan Jamur Candida albicans Menggunakan KOH 10% dan KOH 20%: COMPARISON OF Candida albicans EXAMINATION Using KOH10% and KOH20% - Utami, Rinda Aulia; Kamil, Kamil; Datu, Meiliyawati Tandi (Jurnal Teknologi Laboratorium Medik Borneo, 2024)
Abstract : Fungal diseases affecting the skin, nails, mucous membranes and internal organs caused by various Candida species. Candida albicans is a pathogenic fungus that predominantly infects the urinary tract, genitals, skin and mouth. The most common cause of candidosis is Candida albicans, the species with the highest pathogenicity. Candidiasis on the surface of organs usually only contains a large number of blastospores, in advanced stages only hyphae are seen. If the examination found the presence of Candida sp, it is likely that this yeast is one of the causes of infection. Purpose of the study is to determine the description of the difference in results using 10% KOH and 20% KOH in the examination of Candida albicans fungi. Methods: The type of research conducted was descriptive analytic. The examination was carried out by planting on Sabouraud Dextrose Agar Media and then examining with 10% KOH reagent and 20% KOH. Results from the research conducted on 32 KOH reagent preparations, both are not much different. The difference only lies in the background of the preparation of preparations and the shape of spores and hyphae between using KOH 10% and KOH 20% there is a difference from the background of the preparation. Conclusion the visible hyphae are very fine so that in the preparation of preparations using 10% KOH the hyphae are not clearly visible. In preparations using KOH 20% spores are clearly visible and look full.